2015
DOI: 10.1016/j.ajog.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Estimating systemic exposure to ethinyl estradiol from an oral contraceptive

Abstract: Objectives This study was conducted to compare single-dose pharmacokinetics of ethinyl estradiol in an oral contraceptive to steady-state values, and to assess whether any simpler measures could provide an adequate proxy of the ‘gold standard’ 24-hour steady-state area-under-the-curve. Identifying a simple, less expensive, measure of systemic ethinyl estradiol exposure would be useful for larger studies designed to assess the relationship between an individual’s ethinyl estradiol exposure and her side effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…The level of EE2 in a tablet is, however, a poor indicator of a woman’s individual exposure due to individual differences in absorption and metabolism. Among the women in this study, all taking the same OC, we found the expected greater than two-fold range in steady state 24-hour EE2 exposure (488–1103 pg·h/mL) [25]. However, contrary to expectation, higher individual EE2 exposures were not associated with greater changes in either D-dimer or factor VIII activity.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…The level of EE2 in a tablet is, however, a poor indicator of a woman’s individual exposure due to individual differences in absorption and metabolism. Among the women in this study, all taking the same OC, we found the expected greater than two-fold range in steady state 24-hour EE2 exposure (488–1103 pg·h/mL) [25]. However, contrary to expectation, higher individual EE2 exposures were not associated with greater changes in either D-dimer or factor VIII activity.…”
Section: Discussionmentioning
confidence: 50%
“…D-dimer did not increase 24, 48 and 72 hours after taking the single pill after the 1-month washout period (data not shown). EE2-AUC21 varied from 488 to 1103 pg·h/Ml (data not shown, [25]); change in D-dimer concentration from baseline to OC21 was somewhat correlated with the individual systemic EE2-AUC21 (r = 0.36; 95% CI: −0.21, 0.75; p = 0.21). Figure 3 shows that this association was, however, largely due to the 2 participants whose D-dimer levels decreased substantially after entry to the study; removing these individuals reduced this correlation substantially (r = 0.15; 95% CI: −0.46, 0.67; p = 0.65).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations